Statistically heterogeneous size distribution of ejecta from shock-loaded Cu with a wedged surface groove. (12th January 2016) - He, An-Min; Wang, Pei; Shao, Jian-Li
Abstract: Large-scale molecular dynamics simulations are performed to study the fragmentation of microsheets produced from single crystal Cu with a wedged surface groove. Heterogeneous fragmentation of the microsheet is observed and the ejecta size distribution in the large size limit obeys a bilinear exponential dependence, consistent with the geometric fragmentation model with statistical heterogeneity. The underlying mechanisms governing the statistical heterogeneity are illustrated within the frameworks of geometric fragmentation models.